New Chlorinated Metabolites and Antiproliferative Polyketone from the Mangrove Sediments-Derived Fungus Mollisia sp. SCSIO41409 - Jian Cai; Xueni Wang; Xia Gan; Qian Zhou; Xiaowei Luo; Bin Yang; Yonghong Liu; Disna Ratnasekera; Xuefeng Zhou (Marine Drugs, 2022)
Two new chlorinated metabolites, 8-chlorine-5-hydroxy-2,3-dimethyl-7-methoxychromone (1) and 3,4-dichloro-1H-pyrrole-2,5-dione (3), and eight known compounds (2 and 4–9) were isolated from the mangrove sediments-derived fungus Mollisia sp. SCSIO41409. Their structures were elucidated by physicochemical properties and extensive spectroscopic analysis. The absolute configuration of stemphone C (4) was established for the first time by the X-ray crystallographic analysis. Compounds 3 and 4 showed different intensity of antimicrobial activities against several pathogenic fungi and bacteria, and antiproliferative activities against two human prostate cancer cell lines (IC50 values 2.77 to 9.60 μM). Further, stemphone C (4) showed a reducing PC-3 cell colony formation, inducing apoptosis and blocking the cell cycle at S-phase in a dose-dependent manner; thus, it could be considered as a potential antiproliferative agent and a promising anti-prostate cancer lead compound.